Pengembangan Modul Pembelajaran Ekonomi Berbasis Guided Inquiry Untuk Meningkatkan Hasil Belajar Siswa Kelas Xi MA NW Sukamulia Tahun Pelajaran 2017/2018 - Sholihah, Isfi; Fahrurrozi, Muh (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2017)
This study aims to: 1) analyze the development of guided inquiry-based economic learning module to improve student learning outcomes of grade XI MA NW Sukamulia; 2) to analyze the effectiveness of the use of guided inquiry-based economic learning module to improve student learning result of class XI MA NW Sukamulia.The study of the development of this economic learning module using the modified Borg and Gall procedure consists of 8 stages: 1) preliminary research and information gathering, 2) planning, 3) development of initial product form, 4) limited testing, 5) revision of the main product , 6) extensive test, 7) revision of operational product, 8) field test. Data analysis used during development is descriptive analysis, module feasibility analysis based on criteria score, and analysis of student learning result using t-test.Based on the results of descriptive analysis of economic learning modules based on guided inquiry concluded that the validation of design experts / views as much as 4.6% with good criteria, material experts as much as 3.7% with good criteria. After obtained the validation results can then be done field trials. Based on the results of the experiment, there were 35 complete students and 5 unfinished students with an average score of 81.2% and 87.5% classical percentage. Judging from the results of learning, the use of teaching materials is also an impact on student learning outcomes. This shows that the economic learning module as a result of development can help facilitate the students in learning. Result of questionnaire of student requirement analysis, from 40 respondents obtained total 320 for "yes" response with 80% percentage, and total 90 for "no" category with percentage of 22,5%. The result of questionnaire of student response to economic learning module based on guided inquiry, from 40 respondents obtained total 250 for "yes" response with 73,2% percentage, and total 74 for "no" category with percentage 26,4%. Thus it can be said that the learning module based on guided inquiry get positive response from the students. This shows that the learning module based on the results of economic development further improve the value of students' economic learning outcomes than without using guided inquiry based learning module. The conclusion of this study is a guided inquiry-based economic learning module used to improve student learning outcomes and economic learning modules based on effective guided inquiry to improve learning outcomes.